Fermentative Production of Lactic Acid as a Sustainable Approach to Valorize Household Bio-Waste - Tsapekos, Panagiotis; Alvarado-Morales, Merlin; Baladi, Samin; Bosma, Elleke F.; Angelidaki, Irini (Frontiers in Sustainability, 2020)
Source-sorted organic portion of municipal solid waste (bio-waste) can be fermented to lactic acid, a platform chemical widely used in the production of biodegradable polymers, green solvents and chemicals. In the present study, fermentation of bio-waste using lactic acid producing bacterium (LAB) Lactobacillus delbrueckii was investigated. Results showed that adding 10% (v/v) of L. delbrueckii as LAB inoculum along with pH adjustment to 6.2 had the highest lactic acid yield (0.65 g/g total sugars). Nevertheless, pH adjustment without bio-augmentation could also result in relatively high yield of lactic acid (0.57 g/g total sugars). Furthermore, enzymatic hydrolysis was applied to boost the lactic acid production slightly increasing the yield to 0.72 g/g total sugars. Thus, fermentative production of lactic acid can be achieved without the addition of enzymes to reduce production costs. Overall, the results indicate that bio-waste could be a suitable substrate for the production of lactic acid.